Neuroprotective potential of methanolic leaf extracts of Celosia cristata and Callistemon citrinus on scopolamine-induced amnesia in swiss albino mice - Mishra, Vishwambhar; Chauhan, Bhupendra; Chaudhri, Sanjiv Kumar; Deepika Rani (Journal of Applied Pharmaceutical Research, 2025)
Background: The primary reason for memory loss is Alzheimer’s disease, a progressive neurodegenerative condition in specific brain parts. This study aims to illustrate the relative enhancement of memory, along with the neuroprotective and antioxidant properties of methanolic leaf extracts from Celosia cristata and Callistemon citrinus in scopolamine-induced amnesia in mice. Methodology: Methanolic extracts of the leaves of Celosia cristata and Callistemon citrinus were evaluated for their effects on scopolamine-induced impaired learning and memory in Swiss albino mice using behavioral animal models, including the Morris water maze (MWM), elevated plus maze (EPM), and object recognition task (ORT). Antioxidants such as Superoxide dismutase (SOD), Glutathione peroxidase (GPx), Thiobarbituric acid reactive substance (TBARS), and acetylcholinesterase (AChE) were also assessed at different doses, i.e., 200 and 400 mg/Kg of methanolic extracts of Celosia cristata and Callistemon citrinus, as well as their combinations. Results and Discussion: The various doses of Celosia cristata and Callistemon citrinus methanolic leaf extracts significantly modified scopolamine effects in experimental animals. Extracts significantly decreased escape latency (ELT) in the MWM test. Inflexion ratio (IR) in the EPM test was significantly raised by extracts, as well as the discrimination index (DI) in ORT. The SOD and GPx levels were significantly enhanced whereas TBARS significantly reduced by extracts. The significant reduced level of AChE was reported in extract treated mice. The extracts from both plants exhibited significant results at different doses (200 mg/kg and 400 mg/kg) and combination of both plant extracts (MCel+MCal 400) at 400mg/kg dose showed most significant result. Conclusion: The results revealed that methanolic leaf extracts of Celosia cristata and Callistemon citrinus hold potent antiamnesic effects.